In with the good, out with the bad - Investment standards for external funding of health? - Robert John Fryatt; Mark Blecher (Elsevier, 2023)
In recent decades, external financing of health systems in low- and middle-income countries has helped achieve remarkable improvements across the world. However, these successes have not come without problems. There are a growing number of areas where external assistance can cause harm and even undermine the development of national health systems. Recent decades have seen a surge of knowledge on investing in health systems. We propose the setting up of investment standards for external assistance that aim to incentivize a more efficient evidence-based investment in a country's health system, led by decision-makers in country. Using a more standardized process would lead to a better use of precious external assistance resources. The long-term goal would be fully functioning health systems with all the necessary essential public health functions in all countries.